PENGEMBANGAN MEDIA CONGKLAK MATEMATIKA PADA MATERI PERKALIAN DAN PEMBAGIAN DI KELAS II MIN 2 KOTA MALANG - Nairufashah, Nawan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Multiplication and division are basic materials in mathematics. Students are expected to be able to understand the basic concepts of the material before studying more complex mathematical material. However, based on observations made by researchers, students do not understand the concept of multiplication and division. Apart from that, learning in schools does not yet use media, so researchers provide solutions to develop Congklak Mathematics media on multiplication and division material. The aim of this research and development is to: (1) Find out the procedures for developing valid mathematics congklak media for class II MIN 2 students in Malang City, (2) Find out the attractiveness of mathematics congklak media for class II MIN 2 students in Malang City. The research method used is the research and development method which uses the ADDIE development model. The test subjects in this research were class II C MIN 2 students in Malang City, totaling 27 students. The results of this research are: (1) The final result of the development is Congklak Mathematics learning media on multiplication and division material. The level of validity and feasibility of the Congklak Mathematics developed received a percentage from material experts of 86% in the valid category, a percentage of media experts of 93% in the valid category and a percentage of learning practitioners of 94% in the valid category. (2) The level of attractiveness of the Congklak Mathematics learning media which was developed based on data obtained through a student attractiveness questionnaire received very attractive assessment criteria with an average attractiveness score of 84%. ABSTRAKPerkalian dan pembagian merupakan materi dasar dalam matematika. Siswa diharapkan mampu memahami konsep dasar materi tersebut sebelum mempelajari materi matematika yang lebih kompleks. Akan tetapi, berdasarkan observasi yang dilakukan peneliti, siswa belum memahami konsep perkalian dan pembagian. Selain itu, pembelajaran di sekolah belum menggunakan media pembelajaran sehingga peneliti memberikan solusi untuk mengembangkan media Congklak Matematika pada materi perkalian dan pembagian. Tujuan penelitian dan pengembangan ini adalah untuk: (1) Mengetahui prosedur pengembangan media congklak matematika yang valid untuk siswa kelas II MIN 2 Kota Malang, (2) Mengetahui kemenarikan media congklak matematika untuk siswa kelas II MIN 2 Kota Malang. Metode Penelitian yang digunakan adalah metode penelitian dan pengembangan (Research and Development) yang menggunakan model pengembangan ADDIE. Subjek uji coba pada penelitian ini adalah siswa kelas II C MIN 2 Kota Malang yang berjumlah 27 siswa. Hasil dari penelitian ini adalah: (1) Hasil akhir pengembangan berupa media pembelajaran Congklak Matematika pada materi perkalian dan pembagian. Tingkat kevalidan dan kelayakan dari Congklak Matematika yang dikembangkan mendapat presentase dari ahli materi sebesar 86% dengan kategori valid, presentase dari ahli media sebesar 93% dengan kategori valid dan presentase dari praktisi pembelajaran sebesar 94% dengan kategori valid. (2) Tingkat kemenarikan media pembelajaran Congklak Matematika yang dikembangkan berdasarkan data yang didapatkan melalui angket kemenarikan siswa mendapatkan kriteria penilaian sangat menarik dengan rata-rata nilai kemenarikan sebesar 84%.